Peran Pelabuhan Muara Djati Dalam Islamisasi Di Cirebon - Azizah Khoirotun Nisa (Priangan: Journal of Islamic Sundanese Culture, 2022)
One of the Islamization processes in the archipelago which has an important role is through the port route. Muara Djati Harbor, located in Cirebon, is the gateway to Islamization in West Java. The author uses the historical method, namely a process of study, explanation and critical analysis of the legacy of the past. In this study, the authors used the literature study research category, namely a study that used a source from a book as the data which was then interpreted chronologically to produce historical facts based on the analyzed data. In this study, the author tries to focus on the analysis related to the port of Muara Djati in the Islamization process in Cirebon. Among them is the condition of Muara Djati port before the entry of Islam, the port of Muara Djati's role in the entry of Islam in Cirebon and the port of Muara Djati and the development of Islam in Cirebon. It is known that the condition of the Muara Djati coast before the arrival of Islam, Cirebon people were familiar with the Indianization culture by implementing the caste system. Muara Djati's role in the Islamization process, which became the residence of foreign traders in Cirebon. The development of Cirebon after the entry of Islam affected various aspects of life, people did not feel oppressed because in Islam there was no caste system. The arrival of Syarif Hidayatullah made Cirebon an Islamic sultanate.